Recent advances on research of electrolyzed water and its applications. (October 2021) - Zhao, Lin; Li, Shubo; Yang, Hongshun
Highlights: New and portable electrolyzed water-producing devices and systems were introduced. Antimicrobial factors and mechanisms of electrolyzed water especially from metabolomics analysis were summarized. Combined use of electrolyzed water with other hurdle technologies especially for organic food industry were described. Abstract : As one of the most promising sterilization agents for microbial control in food industry in recent decades, electrolyzed water (EW) can be produced from diluted NaCl solution, and exhibits strong broad-spectrum bactericidal efficiency due to the synergistic effect of available chlorine concentrations, pH and oxidation reduction potential. To date, numerous studies have demonstrated the antimicrobial activity of EW against various kinds of microorganisms both in vitro and in vivo . However, the exact antimicrobial mechanisms of EW have not been determined at present, limiting its widespread application. In this review, we provide an overview of latest production equipment of EW, and briefly summarize the current advances of germicidal factors and antimicrobial mechanisms of electrolyzed water on different states of microorganisms. In addition, studies about hurdle enhancement of EW combined with other technologies are also discussed, providing guidelines for improving food safety and food quality both in conventional and organic food industry.